MEMBANGUN CITRA SELAAWI GARUT SEBAGAI KOTA BAMBU - Santi Susanti; Rachmaniar Rachmaniar (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2022)
This study aims to reveals the efforts of the Government of Garut Regency and Selaawi District in building the image of Selaawi as a Bamboo City. Many bamboo natural resources and skilled human resources in processing bamboo into various crafts with various functions are a great support for achieving Selaawi's dream of becoming a Bamboo City. This study uses a qualitative method with a case study approach. Data  were collected through interviews, observations, and document studies related to efforts to form the image of Selaawi as the City of Bamboo or Dayeuh Awi. The study indicates that building the image of Selaawi as a Bamboo City is a collective effort that requires a long process and the role of many parties to make it happen. Conducting the concept Pentahelix, the government of Garut Regency, especially Selaawi District, works closely with academia, business community, government and media. As a reinforcing force, the Selaawi sub-district government strengthens emotional and community bonds with its citizens to unite to improve their welfare. The Selaawi bamboo craft center building or Selaawi Bamboo Creative Center was built, and the Selaawi Bamboo Festival was held as a medium for promoting bamboo tourism and its own tourist attraction. The image as a Bamboo City is expected to develop the creative economy and tourism of the Selaawi community and become a role model in sustainable bamboo processing and management.